2017
DOI: 10.1016/j.bpj.2017.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of Pore-Spanning Apical Cell Membranes Derived from MDCK II Cells

Abstract: The mechanical response of adherent, polarized cells to indentation is frequently attributed to the presence of an endogenous actin cortex attached to the inner leaflet of the plasma membrane. Here, we scrutinized the elastic properties of apical membranes separated from living cells and attached to a porous mesh in the absence of intracellular factors originating from the cytosol, organelles, the substrate, neighbors, and the nucleus. We found that a tension-based model describes the data very well providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 47 publications
(54 reference statements)
0
29
0
Order By: Relevance
“…Deformation of cells either globally or locally with a sharp indenter is usually interpreted either in terms of a contact mechanics model, providing the Young's modulus, or in terms of a tension model, in which cortical tension prevails at low strain, whereas area dilatation dominates at large strain (11,12). Here, we focus on the apical mechanics of adherent epithelial cells in terms of contact mechanics, in which studies have already shown that the thin actomyosin cortex, together with the plasma membrane of such cells, dominates the repulsive forces that are experienced by nanoindenters (13,14). In epithelial cells, mechanical homeostasis is of major importance and must continue even in challenging environments, e.g., high or low osmolarity, to ensure layer integrity (15).…”
Section: Introductionmentioning
confidence: 99%
“…Deformation of cells either globally or locally with a sharp indenter is usually interpreted either in terms of a contact mechanics model, providing the Young's modulus, or in terms of a tension model, in which cortical tension prevails at low strain, whereas area dilatation dominates at large strain (11,12). Here, we focus on the apical mechanics of adherent epithelial cells in terms of contact mechanics, in which studies have already shown that the thin actomyosin cortex, together with the plasma membrane of such cells, dominates the repulsive forces that are experienced by nanoindenters (13,14). In epithelial cells, mechanical homeostasis is of major importance and must continue even in challenging environments, e.g., high or low osmolarity, to ensure layer integrity (15).…”
Section: Introductionmentioning
confidence: 99%
“…While cells maintain a constant volume during deformation, the basal membrane sheets are physically and chemically attached to the pore rims -the strength of attachment given by equation (24). 19,40,41 The measured area compressibility modulus of the basolateral membrane sheets contains contributions from the rather inexten-sible membrane and the actin mesh. Albeit the outstretched plasma membrane is almost inextensible exhibiting considerable large K A values of 0.1 -0.5 N/m depending on the lipid composition, 42 excess membrane area A ex can be recruited from wrinkles and folds during indentation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our previous publication that simplified the theoretical treatment by assuming that the AFM-indenter can be modelled by a cylindrical flat punch with a small radius of a few nanometers, 28 I now consider a conical indenter and also abandoned the small gradient approximation, which is typically used to simplify the description of the force response. 9,[29][30][31][32] The following treatment is partly inspired by the work of Powers et al 33 who dealt with the formation of tethers pulled from a planar membrane. The free energy of the membrane is given by 34,35…”
Section: Force Response Of Viscoelastic Cortices Spanned Over a Porementioning
confidence: 99%
See 1 more Smart Citation
“…This fitting neglects the bending of the membrane, because the pore radius is greater than the membrane thickness by a factor of >100. [155]…”
Section: Measurement Of Membrane Tensionmentioning
confidence: 99%